FACTOR ANALYSIS OF E-GOV ACCEPTANCE IN SOCIETY AND GOVERNMENT - Prasetyo, Eko; Irawan, Yoan Freddy; Supriyanto, Aji (SOSCIED, 2024)
As governments worldwide increasingly transition towards digital governance, understanding the factors that contribute to the acceptance of Electronic Government (E-Gov) initiatives becomes crucial. This literature review explores various studies conducted on the acceptance of E-Gov by both the public and government entities. The goal is to pinpoint and examine the critical elements that affect the effective deployment and uptake of e-government services. The review encompasses a comprehensive examination of academic articles, research papers, and reports published in the field, covering diverse perspectives such as technological, social, cultural, and institutional factors. Common themes emerge, including the impact of perceived usefulness, ease of use, trust, security, and digital literacy on the acceptance of E-Government services among citizens. Additionally, the literature delves into the challenges and opportunities associated with the government's perspective, highlighting factors such as organizational readiness, policy support, and inter-agency collaboration. By synthesizing findings from various sources, this paper aims to provide a holistic view of the factors shaping the acceptance of E-Government, offering insights for policymakers, practitioners, and researchers. The outcomes of this literature review contribute to the ongoing discourse on enhancing the effectiveness of E-Government initiatives and fostering a digitally inclusive society.